2020
DOI: 10.5194/se-2020-15
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fracture attribute scaling and connectivity in the Devonian Orcadian Basin with implications for geologically equivalent sub-surface fractured reservoirs

Abstract: Abstract. Fracture attribute scaling and connectivity datasets from analogue systems are widely used to inform sub-surface fractured reservoir models in a range of geological settings. However, significant uncertainties are associated with the determination of reliable scaling parameters in surface exposures, particularly for fault widths and fracture aperture. This has limited our ability to upscale key parameters that control fluid-flow at reservoir to basin scales. In this study, we present nine 1D transect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Length distributions are known to be particularly prone to censoring and truncation (Odling et al 1999). However, Odling et al (1999) and Dichiarante et al (2020) have shown that a multi-scale analysis can help to confirm that power-law scaling is an appropriate choice to model the fracture length distributions. In the present study, the basement fracture lengths sampled in 1D show a scaling relationship across 8 orders of magnitude and the 2D sample windows show consistent and comparable length distributions between onshore and offshore datasets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Length distributions are known to be particularly prone to censoring and truncation (Odling et al 1999). However, Odling et al (1999) and Dichiarante et al (2020) have shown that a multi-scale analysis can help to confirm that power-law scaling is an appropriate choice to model the fracture length distributions. In the present study, the basement fracture lengths sampled in 1D show a scaling relationship across 8 orders of magnitude and the 2D sample windows show consistent and comparable length distributions between onshore and offshore datasets.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when large fractures are incompletely sampled in a power-law population, the resulting plot can resemble a log-normal distribution. Following Ortega et al (2006), Dichiarante et al (2020) have shown how a multi-scale approach can be used to better constrain the scaling laws for fracture size attributes. As pointed out by Clauset et al (2009), use of the maximum likelihood estimator (MLE) is preferred over a least square regression analyses (R 2 ) for the fitting of power-law distributions.…”
Section: Fracture Sizesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regards, a possible explanation to the finding that "upper cut has a greater influence over the sample fit". This outcome is a direct result of the current method used in Rizzo et al (2017a) and Healy et al (2017) to find the best fitting law (which follows Clauset et al, 2009): this method looks for that minimum value (xmin) for which the theoretical distribution law will hold (either Power-law, Lognormal, or Exponential). Large values therefore, do not influence the fitting.…”
Section: Interactive Commentmentioning
confidence: 99%